The power of the press photo. Analysis of the pictures coverage of the refugee crisis in the ABC newspaper - López Marrupe, Isabel (Revista Española de Comunicación en Salud, 2019)
In 2015 more than 65 million people around the world were forced to leave their homes. It was the refugees´s year. Also it was the year of Aylan’s death. The photograhy of his body went around the world and removed the collective consciousness of a society immune to the suffereing of others. It was a decisive change in the media coverage of conflict. The objective of this research is to study what was the effect of this picture. For this reason, we will analyze the coverage through pictures in the ABC newspaper. Through this study we verified how Aylan’s photography managed to change of newspapers discourse, but this effect didn´t last for too long. Apart from this the massive consumption of pictures caused a false illusion about the conflict, when actually citizens perceived only part of the complex conflict. Also, we prove how the incorrect use of the terms “refugee” and “immigrant” affects the negative image that the society perceives of this humanitarian conflict. A fact of special relevance considering the public service of the journalists and their ethical criteria.
Keywords: Refugee crisis; Fotography; Humanitarian crisis; Immigration; ABC newspaper